Effect of artificial liver blood purification treatment on the survival of critical ill COVID‐19 patients. Issue 7 (21st March 2021) - Dai, Xiahong; Zhang, Yimin; Yu, Liang; Jiang, Ying‐an; Chen, Liang; Chen, Ye; Li, Ming; Gao, Chunming; Shang, Jia; Xiang, Shulin; Li, Yongguo; Li, Jianzhou; et al.
Abstract: Our aim was to investigate the effect of artificial liver blood purification treatment on the survival of severe/critical patients with coronavirus disease 2019 (COVID‐19). A total of 101 severe and critical patients with coronavirus SARS‐CoV‐2 infection were enrolled in this open, case‐control, multicenter, prospective study. According to the patients' and their families' willingness, they were divided into two groups. One was named the treatment group, in which the patients received artificial liver therapy plus comprehensive treatment ( n = 50), while the other was named the control group, in which the patients received only comprehensive treatment ( n = 51). Clinical data and laboratory examinations, as well as the 28‐day mortality rate, were collected and analyzed. Baseline data comparisons on average age, sex, pre‐treatment morbidity, initial symptoms, vital signs, pneumonia severity index score, blood routine examination and biochemistry indices etc. showed no difference between the two groups. Cytokine storm was detected, with a significant increase of serum interleukin‐6 (IL‐6) level. The serum IL‐6 level decreased from 119.94 to 20.49 pg/mL in the treatment group and increased from 40.42 to 50.81 pg/mL in the control group ( P < .05), indicating that artificial liver therapy significantly decreased serum IL‐6. The median duration of viral nucleic acid persistence was 19 days in the treatment group (ranging from 6 to 67 days) and 17 days in the control group (ranging from 3 to 68 days), no significant difference was observed ( P = .36). As of 28‐day follow‐up, 17 patients in the treatment group experienced a median weaning time of 24 days, while 11 patients in the control group experienced a median weaning time of 35 days, with no significant difference between the two groups ( P = .33). The 28‐day mortality rates were 16% (8/50) in the treatment group and 50.98% (26/51) in the control group, with a significant difference ( z = 3.70, P < .001). Cytokine storm is a key factor in the intensification of COVID‐19 pneumonia. The artificial liver therapy blocks the cytokine storm by clearing inflammatory mediators, thus preventing severe cases from progressing to critically ill stages and markedly reducing short‐term mortality. Abstract : The artificial liver blood purification treatment blocks cytokine storm by clearing inflammatory mediators such as IL‐6, thus preventing severe cases from progressing to critically ill stage and remarkably reducing the short‐term mortality.